The importance of finance and banking marketing in the present conditions - PISTOL, Gheorghe (Annals of Spiru Haret University. Economic Series, 2016)
Taking into consideration the complexity and dynamics of economic and social life, in general, and especially actual environment which the economic entities and, particularly, the financial and economic crisis facing humanity, the role and the importance of marketing in the financial-banking activities is growing. This role is referring at: actual economic and social dynamism, providing financial and banking liquidity, managing financial and banking risk and customer operations. Responsible for the increased importance of the current banking and financial marketing are factors such as: significant increase in the services sector, in general, and banking one, in particular; complexity and dynamic of marketing environment, especially, the banking sector, increased competition regarding this area and, not least, the effects of the current crisis. In such a context, significant efforts are required towards the improvement of marketing activity, both macroeconomic and banking units in each part.